Formation of keteniminium salts:|mechanistic aspects and effect of substituents - Aktaş, Zeynep. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Most organic reactions occur in several consecutive steps that include the generation of highly reactive intermediates, which are short-lived. Keteniminium salts (KI) are key and versatile intermediates in synthetic organic chemistry that are used in various reactions, such as [2+2] and [4+2] cycloadditions, Pictet{Spengler cyclization, Claisen-like rearrangements. Elucidation of the mechanistic aspect of these KI formation reactions ensures the understanding of the formation of this intermediate. In this study, to provide a comprehensive understanding of the KI formation, various formation mechanisms were investigated, using density functional theory (DFT). Particularly, Ghosez's formation mechanism was extensively elaborated since Ghosez's reaction occurs in mild conditions and is the most frequently used experimental method. Moreover, a broad range of substituents was examined to give perspective to the possible contributions of the substituents. The e ect of these substituents on the reactivity of starting amides was also inspected using population analysis, distortion/interactionactivation strain model analysis, non-covalent interaction (NCI) analysis. In the nal part of the study, the substituent effect on corresponding KIs is also investigated in the frame of Conceptual DFT. Computed data showed that, in general, electron-donating groups (EDGs) decrease the activation barrier by increasing the electron density of the amide carbonyl oxygen in contrast to electron-withdrawing groups (EWGs). Besides, according to the distortion/interaction-activation strain model and NCI analysis, electronic and steric effects are notable factors on electrophilic activation of the starting amide during KI formation. This study will contribute a pivotal insight into the mechanistic aspects of the KI formation and the role of the substituents.